Performance assessment and optimization of two novel cogeneration systems integrating proton exchange membrane fuel cell with organic flash cycle for low temperature geothermal heat recovery. (15th March 2022) - Yu, Zeting; Feng, Chunyu; Lai, Yanhua; Xu, Guoping; Wang, Daohan
Abstract: In order to realize the collaborative utilization of the low-grade geothermal energy and proton exchange membrane fuel cell (PEMFC) waste heat, this study proposes two novel combined systems integrated PEMFC with organic flash cycle (OFC) driven by geothermal energy. And the proposed systems are named as the enhanced power generation (EPG) cycle which can produce more electricity output, and the combined cooling and power (CCP) that can provide more cooling capacity. The thermodynamic and economic models are established to study the combined system performance. And the results show that under given conditions, the total thermal efficiency of EPG and the CCP achieves 8.50% and 8.83%, while the total exergy efficiency is 36.77% and 34.11%, respectively. The exergy analysis shows that the components with the major exergy destruction in these two systems are flashers, condensers and boilers. Parameter analysis shows that the heat source temperature, condensation temperature, fuel cell operating temperature, operating pressure and current density have the key impacts on the proposed system performance. Furthermore, the multi-objective optimization and decision making for the two combined systems are carried out. And the five Pareto frontiers with different organic working fluids (R600, R123, isobutene, R245fa and butane) are obtained. Highlights: Two novel combined systems for geothermal energy recovery are proposed. The fuel cell stack is uniformly cooled by the organic working fluid. Detailed exergy analysis and parameter analysis are conducted. Pareto frontiers with different organic working fluids are obtained.